The Reproductive Capacity and Nutritive Value of Calligonum Polygonoides Linn. - Bishnoi, S; Gautam, D D (Annals of Arid Zone, 2016)
Caligollllm polygolloides Linn. is monoembryonic and endospermic having epigeal germination. Natural plant populations have three categories of seeds: large, medium and small. The optimum temperature for seed germination in petri dishes was 20 ±20 C. The average percentage germination was 68.0 ± 5.35. The average seed output was very high (38177 ± 15469) and varied with the size of the plant. The reproductive capacity was 25960 as the seed/fruits were damaged by the insects even before ripening and shedding. The endosperm of the seed contained starch (37.25%) and crude protein (12.9%).